Zameczek w Wojsławicach - Augustyniak, Jerzy (Biuletyn Szadkowski, 2010)
Wojsławice is a small village situated about 5 km south-west of Szadek, by an old (13th century) road to Sieradz. Archeological works conducted in the early 1970s resulted in a discovery of an object that had hitherto been unknown. In the second half of the 16th century the family of Wężyk built on an island surrounded by a pond a small castle (21m x 23 m) with a semicircular tower in the north-east corner. The south side of the premises was formed by a two-storey dwelling-house 23 m x 8.9 m large. The courtyard was surrounded by a defensive wall 2 m–2.2 m thick. The castle was built of bricks on stone foundations. It was created at a time when Szadek was in the brightest period of its history.